Nigerian national merit awards : award winners' lectures - Nigerian National Merit Awards Endowment Fund; Nigerian National Merit Award Endowment Fund. (Ikeja : Longman Nigeria Ltd., 1985)
This book contains mainly accounts to past achievements and work. It gives account of Nigerian history of intellectual, technological, scientific and cultural movement of Nigerians citizens.
usc 03/11/2021
Ref.
Keywords: Nigeria